Nano catalysts in effective biomass processing - Srijita Dutta (International Journal of Pharmacy and Analytical Research, 2015)
The population of the world is increasing day by day very rapidly and the development in industrial field raise the demand of energy. Due to limited resource of non-renewal energy resource, hike in crude oil prices and ever increasing pollution, human civilization has been forced to look for renewal energy recourses and hence biomass has got a great attention in this regard. Currently biomass is supplying about 10-15% energy of the world and it is expected to contribute half of the energy of the whole world by the year 2050. Biomass is generally processed by gasification and direct liquefaction to produce gases and liquids used as energy, but it also has to face the problems caused by heterogeneous catalyst, in the form of increase in material cost, decrease of catalyst performance over the time, the relative difficulty in reclaiming and recycling, sulfur poisoning and deactivation. Nano technology has shown a promising hope in this regard. Gasification provides a route in converting the highly distributed and low value lignocellulosic biomass to hydrogen rich gas, namely the synthetic gas, as well as hydrogen gas. Moreover, the resulting gas achieves a Fischer-Tropsch reactor favourable H2: CO ratio of about 9:1. The application of nanocatalysts improves yield at relatively milder operating conditions compared to bulk catalyst. Moreover nano catalysts are economically feasible on large scale with respect to heterogeneous catalyst. Also, the nano catalysts NiO, CeO2, ZnO, and SnO2 are used to reduce tar formation during gasification. The nano catalyst treatment increases gas yield and, in one embodiment, cracks and gasifies lignin, which is generally inert in conventional gasification. The nanoalloy catalysts like CeZr, xO2 and Ni3Cu (SiO2)6 achieve the increased conversion efficiency and cracking of any biomass at relatively lower gasification temperature. As such combination of catalyst and methods invented till now, provides a means to increase gas yields while lowering the lignin content in the resulting product relative to conventional gasification.